Components of water management for human consumption in the Municipality of Valle de Angeles, Honduras - Sosa Pérez, Gabriel (CATIE, Turrialba (Costa Rica), 2014)
Tesis (M. Sc) -- CATIE, Turrialba (Costa Rica), 2007